1998
DOI: 10.1124/mol.53.2.195
|View full text |Cite
|
Sign up to set email alerts
|

dl-threo-β-Benzyloxyaspartate, A Potent Blocker of Excitatory Amino Acid Transporters

Abstract: DL-threo-beta-Benzyloxyaspartate (DL-TBOA), a novel derivative of DL-threo-beta-hydroxyaspartate, was synthesized and examined as an inhibitor of sodium-dependent glutamate/aspartate (excitatory amino acid) transporters. DL-TBOA inhibited the uptake of [14C]glutamate in COS-1 cells expressing the human excitatory amino acid transporter-1 (EAAT1) (Ki = 42 microM) with almost the same potency as DL-threo-beta-hydroxyaspartate (Ki = 58 microM). With regard to the human excitatory amino acid transporter-2 (EAAT2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
478
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(501 citation statements)
references
References 37 publications
19
478
3
1
Order By: Relevance
“…Regarding extended stimulus trails, the nontransportable inhibitor of glutamate uptake (TBOA; Jabaudon et al, 1999;Shimamoto et al, 1998) did not decrease the overshoot signal after extended stimulation (Figure 10). The concentration of TBOA used here (100 mmol/l) was the same as that used to block glial depolarizations evoked by synaptic stimulation in hippocampal slices (Kawamura et al, 2004).…”
Section: Glutamate Uptakementioning
confidence: 98%
“…Regarding extended stimulus trails, the nontransportable inhibitor of glutamate uptake (TBOA; Jabaudon et al, 1999;Shimamoto et al, 1998) did not decrease the overshoot signal after extended stimulation (Figure 10). The concentration of TBOA used here (100 mmol/l) was the same as that used to block glial depolarizations evoked by synaptic stimulation in hippocampal slices (Kawamura et al, 2004).…”
Section: Glutamate Uptakementioning
confidence: 98%
“…The release of glutamate was monitored by the use of the nonmetabolizable glutamate analog D-[ 3 H]aspartate, which labels the vesicular as well as the cytoplasmic glutamate pools (Belhage et al, 1992;Cousin and Nicholls, 1997;Fleck et al, 2001). To examine a possible contribution of the transporters to the release of D-[ 3 H]aspartate, the nontransportable glutamate transport inhibitor DL-threo-b-benzyloxyaspartate (TBOA) was employed (Shimamoto et al, 1998;Waagepetersen et al, 2001;Bak et al, 2003Bak et al, , 2004. To assess the relative importance of glucose and lactate as substrates for neuronal metabolism, the cultures were superfused in media containing either [U-13 C]glucose (2.5 mmol/L) and lactate (1 or 5 mmol/L) or [U-13 C]lactate (1 mmol/L) and glucose (2.5 mmol/L).…”
Section: Introductionmentioning
confidence: 99%
“…However, TSC2 GFAP CKO mice have an earlier onset (3 weeks in TSC2 GFAP CKO vs 4 weeks in TSC1 GFAP CKO) and higher frequency of seizures (30)(31)(32)(33)(34)(35) Sz/48 h at 7 weeks in TSC2 GFAP CKO vs less than 10Sz/ 48 h at 7 weeks in TSC1 GFAP CKO), and significantly more severe histological abnormalities. The differences between these 2 transgenic mice seem to be correlated with higher levels of mTOR activation in TSC2 GFAP CKO mice.…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 96%
“…The authors concluded that partial seizures that are best characterized by rhythmic slow oscillations in 1 territory of the brain are most likely due to poor axonal myelination. The use of threo-beta-benzyloxyaspartate to modify glutamate transport has several advantages: threo-betabenzyloxyaspartate is a nontransportable inhibitor and, as such, does not induce artificial transmitter release through hetero exchange and does not act as a partial agonist of glutamate receptors (these properties were demonstrated with electrophysiological recordings and binding assays) [34]. They demonstrated the role of glutamate receptor activation in the generation of the EEG pattern by modifying the frequency and duration of activation by administering the N-Methyl-D-aspartate (NMDA) antagonist ketamine or the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) antagonist NBQX [33].…”
Section: Neonatal Epileptic Encephalopathies With Suppression Burstmentioning
confidence: 99%